2017
DOI: 10.1007/s10552-017-0901-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of obesity-related markers and risk of renal cell carcinoma in the PLCO cancer screening trial

Abstract: Purpose Obesity is an established risk factor for renal cell carcinoma (RCC). It is unclear what biologic mechanisms underlie this association, although recent evidence suggests that the effects of circulating hormones such as insulin-like growth factors (IGF) and adipokines may play a role. Methods To address this question we conducted a nested case-control study of RCC (252 cases, 252 controls) within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial investigating associations with pre-diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Of them, 11 were further excluded because 3 of them reported overall cancer risk rather than RCC risk; 1 reported cancer mortality rather than RCC risk; 2 did not measure circulating adiponectin; 2 were reports of the same cohorts; and the other 3 did not include control groups of healthy participants. Finally, 8 studies [14][15][16][17][18][19][20][21] were included.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Of them, 11 were further excluded because 3 of them reported overall cancer risk rather than RCC risk; 1 reported cancer mortality rather than RCC risk; 2 did not measure circulating adiponectin; 2 were reports of the same cohorts; and the other 3 did not include control groups of healthy participants. Finally, 8 studies [14][15][16][17][18][19][20][21] were included.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…In a few pilot studies, lower circulating adiponectin was observed in RCC cases than in healthy controls, [14][15][16][17] while no significant difference of circulating adiponectin was observed between RCC cases and controls in some other studies. [18][19][20][21] The inconsistency of these findings may be explained by the differences of study population and sample sizes of the studies. A previous meta-analysis by Yap et al 22 included seven studies [14][15][16][18][19][20][21] and concluded that patients with RCC had lower circulating adiponectin than healthy controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating IGF-1, adiponectin, and others (IGFBP-3, HMW adiponectin) were also investigated in relation to renal cell carcinoma (RCC) risk, in a prospective study within the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trials (a population-based multi-center randomized screening trials in the US) [ 127 ]. Data, however, did not provide definite evidence of the starting hypothesis, although the authors observed a weak association between adiponectin and IGFBP-3.…”
Section: Igf-1 and Adiponectin In Relation To Cancermentioning
confidence: 99%
“…Data, however, did not provide definite evidence of the starting hypothesis, although the authors observed a weak association between adiponectin and IGFBP-3. In particular, high adiponectin and HMW adiponectin levels were related to a reduced RCC risk; on the contrary, high IGF-1 and IGFBP-3 levels suggestively increased RCC risk [ 127 ].…”
Section: Igf-1 and Adiponectin In Relation To Cancermentioning
confidence: 99%